2017
DOI: 10.24966/fsn-1076/100015
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Extraction Optimization of the Antioxidant and Antihyperglycemic Components of Boscia Senegalensis Using Central Composite Design Methodology

Abstract: 10 min extraction time. At this optimum point the polyphenol content, total reducing power, DPPH free radical scavenging and glycemic index were respectively 2.34 mg galliceq/100 mL, 0.41 mg vitamin C eq/100 mL, 59.0% and 51.6%. In conclusion the response surface methodology successfully conducted to production of decoction of Boscia senegalensis with the highest polyphenol content, antioxidant properties and the lowest glycemic index.Keywords: Antioxidant propertie; Boscia senegalensis; Decoction; Glycemic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Then, it has also been showed that the aqueous, alcoholic, and hydroalcoholic extracts of the fruits of Dichrostachys glomerata, which is the second plant of medicinal interest of the study, exhibit antioxidant (Kuate, Etoundi, Soukontoua, Ngondi, & Oben, 2010), anti-hypertensive, hypoglycemic (Fankam, Kuete, Voukeng, Kuiate, & Pages, 2011), anti-inflammatory, and anti-hyperlipidemic activities (Kuate et al, 2013); these numerous biological activities were attributed to their contents in a broad range of bioactive molecules such as alkaloids, saponins, tannins, mucilage, glucocapparins, and sterols. Likewise, the seed extracts of the third plant of medicinal interest of the current study, Boscia senegalensis, are rich in saponins, tannins, anthraquinone, alkaloids, and flavonoids; it has been shown that they have anti-inflammatory, anti-hyperglycemic, and antioxidant properties (Dongmo, Dogmo, & Njintang, 2017).…”
mentioning
confidence: 93%
“…Then, it has also been showed that the aqueous, alcoholic, and hydroalcoholic extracts of the fruits of Dichrostachys glomerata, which is the second plant of medicinal interest of the study, exhibit antioxidant (Kuate, Etoundi, Soukontoua, Ngondi, & Oben, 2010), anti-hypertensive, hypoglycemic (Fankam, Kuete, Voukeng, Kuiate, & Pages, 2011), anti-inflammatory, and anti-hyperlipidemic activities (Kuate et al, 2013); these numerous biological activities were attributed to their contents in a broad range of bioactive molecules such as alkaloids, saponins, tannins, mucilage, glucocapparins, and sterols. Likewise, the seed extracts of the third plant of medicinal interest of the current study, Boscia senegalensis, are rich in saponins, tannins, anthraquinone, alkaloids, and flavonoids; it has been shown that they have anti-inflammatory, anti-hyperglycemic, and antioxidant properties (Dongmo, Dogmo, & Njintang, 2017).…”
mentioning
confidence: 93%